Theoretical Aspects of Spinal Osteochondrosis Patient Psychological Characteristic Study - Timur Med'khatovich, Nurakhmetov (2020)
Spinal osteochondrosis is an urgent problem of modern medicine, sociology, psychology, and a number of other disciplines. The interdisciplinary status of degenerative-dystrophic diseases of the spine is indicated by the fact that they are a manifestation of both a number of somatic and neurological diseases. Every year the number of patients with this pathology rapidly grows. According to studies, they affect up to 90-97% of the adult population and represent an economic burden, since rehabilitation treatment of patients involves significant financial costs. The article provides a theoretical analysis of existing studies related to the study of the influence of individual psychological characteristics of patients with spinal osteochondrosis.